Current Sheet Thinning in the Wake of a Bubble Injection. Issue 24 (26th December 2022) - Wang, Wenrui; Yang, Jian; Toffoletto, Frank R.; Wolf, Richard A.; Nakamura, Rumi; Cui, Jun
Abstract: A crucial property of the substorm growth phase is the current sheet thinning, which is often attributed to adiabatic convection. Injecting low‐entropy bubbles reduce pressure‐balance inconsistencies and restore current sheet thickness to its initial value. Recent observations from Cluster and MMS showed additional thinning of the current sheet in the wake of a transitory bubble injection compared with the configuration before the injection. We employ the Rice Convection Model‐MHD coupled code to investigate how the transport of bubbles causes the fast thinning. The simulation results reconstructed the observations' most prominent characteristics. We find more earthward transport of the magnetic flux in the bubble than its wake, therefore depleting magnetic flux and stretching the magnetic field lines there. Interestingly, additional R0‐sense field‐aligned currents close the enhanced dawn‐to‐dusk current behind the bubble. Plain Language Summary: Geomagnetic activity is accompanied with significant energy conversion in near Earth space. One of the most important processes is referred to as "auroral substorms, " which involve magnificent display of aurora borealis in the high latitude regions. In the early stage of a substorm, magnetic energy is accumulated in the nightside of the near‐Earth environment. At the same time, a dawn to dusk electric current gradually becomes very thin. Later, the magnetic energy is transferred to the Earth by particle injections from the nightside, powering the aurora and thickening the current sheet. However, our research indicates that certain transient injections can actually stretch the magnetic field lines behind them, resulting in a much thinner current sheet. Our simulation demonstrates that the injection depletes the magnetic flux and thus weakens magnetic field strength in its wake. The dawn‐to‐dusk electric current is enhanced accordingly in the region of the thinned sheet, and a magnetic‐field‐aligned current system forms to connect that current with the ionospheric current. Key Points: We use the Rice Convection Model‐MHD coupled code to simulate a transient bubble injection in the plasma sheet Localized earthward flux transport leads to substantial thinning in the wake of the bubble, consistent with MMS and Cluster data The enhanced dawn‐to‐dusk current behind the bubble is closed with additional field‐aligned currents